Integrating Digital Archives and Artificial Intelligence: A Conceptual Model for Inquiry-Based Local History Education - Dimas Anggoro (Universitas Negeri Semarang, 2025)
This conceptual study explores the integration of Artificial Intelligence (AI) and digital archives to develop an innovative inquiry-based learning model for local history education within Indonesia's Merdeka Curriculum. Through a systematic literature review, the research examines how AI tools like ChatGPT and Google Lens can mitigate challenges in source access and analysis, thereby fostering students' critical thinking, analytical reasoning, and historical literacy. The proposed model leverages digital archives to provide contextualized primary sources, while AI acts as a cognitive scaffold to support hypothesis formulation, text interpretation, and evidence evaluation. Findings suggest that this synergistic approach can transform students from passive recipients into active historical investigators, enabling meaningful engagement with local narratives. The study contributes to discourse on pedagogical innovation, digital resource utilization, and the development of 21st-century historical competencies in post-colonial educational settings.